(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
This article aims to analyze cost management in the most capitalized restaurants in Cúcuta, Norte de Santander, Colombia. To achieve this objective, the management of production costs of dishes by the managers is identified. Following a quantitative research approach, supported by an exploratory and descriptive phase, a questionnaire consisting of 60 items was administered to a sample of twenty-one restaurants belonging to the Colombian Association of the Gastronomic Industry (ACODRÉS) - Cúcuta. The results indicate that some companies are not adequately managing costs related to materials, labor, and indirect manufacturing costs. This issue hinders the achievement of appropriate efficiency levels.